الحديث النبوي الشريف وأثره في تطوير اللغة العربية - ناصر الدين إبراهيم أحمد (‘Abqari Journal, 2015)
The relationship between the Hadīth and the Arabic language is a very close relationship, one of it cannot be separated of another; in acoustic, morphological, compositional, semantic and other issues. The Prophet (PBUH) is an Arab, the Holy Qur’ān that was revealed to him and his speeches cannot be understood properly except in Arabic. Based on the relationship between the Hadīth and the Arabic language, the researcher in this brief article highlights the impact of the Hadīth in Arabic language in general, and the Arab dictionaries in particular. This article deals with the views of scholars regarding using the Hadīth as an evidence, and also the impact of the Hadīth in different linguistic aspects; like the impact of Hadīth in the development of language, its impact in enriching the new wording of the Arabic language and its impact in the Arab dictionaries.